Penerapan Model Pembelajaran Discovery Learning Pada Materi Asam dan Basa Untuk Meningkatkan Hasil Belajar Siswa Kelas XI SMA N 1 Tareran - Sinaulan, Petra; Krisen, Sofia; Paat, Vlagia (Chemistry Department, Universitas Negeri Manado, 2025)
This research aims to determine the improvement of student learning outcomes through the application of the Discovery Learning model in the acid and base material of class XI SMA Negeri 1 Tareran in the 2023/2024 school year. This type of research is Classroom Action Research. The subjects in this study were 11th grade students of SMA Negeri 1 Tareran, totaling 12 students. This research includes 4 stages (1) planning stage, (2) implementation, (3) observation, (4) reflection. Data collection methods used in this study were observation method, and post-test. The results showed that with the Discovery Learning learning model there was an increase in student learning outcomes, namely from cycle I 73.91%. In cycle II with improved actions in the form of learning activities by dividing students into groups, students conduct discussions according to the learning material, namely acids and bases, students work together, students collect discussion results and make conclusions with guidance from the beginning to the end of learning activities, there was an increase from 73.91% to 85.5%.